The competitiveness and efficiency of paddy growers at Merbok, Kedah / Mohammad Ikmal Aliff Mohd Adly - Mohd Adly, Mohammad Ikmal Aliff (Faculty of Plantation and Agrotechnology, 2018)
Rice is a crop that is included as a major crop in Malaysia and rice is a major source of food consumed by Malaysians as well as a staple food. Production of rice should be justified in line due to high demand and population increased. Paddy crops in our country only for self-sufficiency of Malaysians people and required import from neighbouring country about 30 %. This survey is to find out the problem that blocking for maximum yields of farmers which consist the factor of water management, attitudes of farmers, knowledge of farmer in blast disease control and last factor is acidic soil. The objectives are to assess the level competitiveness and efficiency of farmers at Merbok, to evaluate problem faced by farmer at Merbok regarding to level competitiveness and efficiency of farmers and last objectives is to determine the most influenced factor for maximum yield of farmers towards competitiveness and efficiency of farmers at Merbok. The study was focused on Merbok, Kedah and 175 respondents were identified to be asked by using questionnaires and interview. This study was carried out using a questionnaire distributed to the respondents and the results were analysed using the reliability test, descriptive analysis, Pearson correlation and multiple linear regression analysis using Statistical Package for Social Science (SPSS). However, the results show level competitiveness and efficiency of paddy growers still low and not reach government target. Meanwhile, the correlation results showed only two correlations which are attitudes of farmers and knowledge of farmers in blast disease control between maximum yield of farmers. The results for multiple linear regression which is most influenced factor is knowledge of farmers in control blast disease and second influenced factor is an attitudes of farmers about mean 7.00 % affect the maximum yields of farmers and another 93.00% is caused by other factors.